Evaluation of Laser Doping of Si from MCLT Measurement (Baghdad Science Journal, 2004)
The measurement of minority carrier lifetime (MCLT) ofp-n Si fabricated with aid of laser doping technique was reported. The measurement is achieved by using open circuit voltage decay (OCVD) technique. The experiment data confirms that the value of MCLT and proftle of Voc decay were very sensitive to the doping laser energy.